2018
DOI: 10.3390/ijerph15061132
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Housing and Community Conditions on Multidimensional Health among Middle- and Low-Income Groups in Hong Kong

Abstract: With decades of urbanization, housing and community problems (e.g., poor ventilation and lack of open public spaces) have become important social determinants of health that require increasing attention worldwide. Knowledge regarding the link between health and these problems can provide crucial evidence for building healthy communities. However, this link has heretofore not been identified in Hong Kong, and few studies have compared the health impact of housing and community conditions across different income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…According to prior research [7][8][9], mental health variables included stress, anxiety, and depression in this paper. For stress, participants were asked "How often do you feel stressed during the last year?"…”
Section: Outcome Variables: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…According to prior research [7][8][9], mental health variables included stress, anxiety, and depression in this paper. For stress, participants were asked "How often do you feel stressed during the last year?"…”
Section: Outcome Variables: Mental Healthmentioning
confidence: 99%
“…As for mental health, many previous studies have investigated the effects of housing status on self-rated general mental health. According to past research [7][8][9], individuals' mental health can be represented by different aspects such as stress, anxiety, and depression. Yet, mixing these aspects or only using an aggregated index/score (i.e., self-rated general mental health) may not be conducive to clarifying the impacts of housing status on mental health.…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…In Hong Kong, studies that focused on the association between housing and mental wellbeing are limited, with a few exceptions (Cheung, Tsoi, Wong, & Chung, 2019; Chung et al., 2020; Lam et al., 2015; Ng, Zhang, Ng, Wong, & Lee, 2018; Wang, Huang, Zhang, Wong, & Huang, 2018). In particular, Chung et al.…”
Section: Introductionmentioning
confidence: 99%
“…Gou, Xie, and Lu (2018) found that housing environment is the most influential factor and has a negative effect on the overall quality of life for public rental housing residents. Wang, Huang, Zhang, Wong, and Huang (2018) reported that the influence of housing environment on chronic diseases is more sensitive for low-income group than the entire population. Forrest, LaGrange, and Yip (2004) argued that the relationship between the concentration of deprivation and spatial location is not statistically significant.…”
Section: Local Studies In Hong Kongmentioning
confidence: 99%